PENINGKATAN SOSIOEKONOMI MASYARAKAT MELALUI PELATIHAN DISPLAY TOKO BAGI GALERI UMKM TP PKK KABUPATEN LUMAJANG - Fahrullah,; yasin, ach .; Ridlwan, Ajib; Fikriyah, Khusnul; Indrarini, Rachma; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2023)
Micro, Small and Medium Enterprises or commonly called UMKM is one of the driving wheels of the economy in Indonesia, especially in Lumajang district. The increasing number of MSMEs from year to year shows that the majority of people in Lumajang are starting to wish to create their own business. However, the obstacle that is often faced by business actors in Lumajang is their lack of ability to distribute their products. Low knowledge about product displays is a problem and has an impact on low product value and is less desirable. To overcome this, product display training is carried out. The method used is training delivered offline. The result of this activity is an increase in the participants' knowledge and ability to display products. This is known from the responses of the participants to the questionnaire given which showed the results that all participants agreed that the material provided was useful and had an impact on increasing the participants' knowledge.